As políticas públicas da assistência social: o centro de referência da assistência social de Abaetetuba e as ações de intervenção às crianças e adolescentes em riscos e vulnerabilidades - SILVA, Valdinéia Ferreira da (2019)
The present work has the theme Public Policies of Social Assistance: Abaetetuba Reference Center for Social Assistance and actions to intervene children and adolescents in risks and vulnerabilities. Its main objective is to investigate the socio-educational practices carried out in the Seeds of Tomorrow Project through the social programs of CRAS-São Sebastião together with the Social Assistance Secretariat. Having as specific objectives To identify through the experiences of the agents involved in the research (student, former student, social educator) the importance of the Seeds of Tomorrow project and how it has contributed in the development of potentialities, abilities, talents of children and adolescents. The research methodology was based on field research, interviews, photographic records and literature review. The research was carried out at the São Sebastião CRAS in Abaetetuba that serves people in vulnerability and social risk. The results allow us to infer that it is extremely important the work developed through socio-educational practices developed in the Seed Project of Tomorrow, since it gives children and adolescents an understanding of the importance of experiencing values and principles in family, group and social coexistence, relating rights and as a focus of prevention and protection.